2003
DOI: 10.1177/0047287502239032
|View full text |Cite
|
Sign up to set email alerts
|

Internet Technology Use by American Convention and Visitors Bureaus

Abstract: Adoption and diffusion theories are used to explain key factors affecting the use of Internet technology by American convention and visitors bureaus. Organizational properties, leader characteristics, and technology-activity fit are assumed to determine the extent and length of information technology (IT) use. A survey conducted among American convention and visitors bureaus indicates that bureaus can be classified into five adopter groups (laggards, sophisticated followers, knowledge adopters, early light ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 38 publications
7
63
0
1
Order By: Relevance
“…Some have considered various combinations of these two types of measures (see Zhuang & Lederer, 2006), (Salwani et al, 2009). Nonfinancial measures of e-commerce value include the efficiency of operations, improvements in business relationships, market growth (Pflughoeft et al, 2003), (Zhu and Kraemer, 2005), (Zhu et al, 2006), (Fuchs et al, 2010), contributions of e-commerce to the achievement of organizational goals, the number of visitors to a particular site, the amount of time visitors spend on a particular site (Quaddus & Achjari, 2005), strategic benefits (Pflughoeft, 2003), the number of applications used (Yuan et al, 2003), and competitive advantage (Elly & Boter, 2011).…”
Section: Effects Of E-commerce On Firm Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Some have considered various combinations of these two types of measures (see Zhuang & Lederer, 2006), (Salwani et al, 2009). Nonfinancial measures of e-commerce value include the efficiency of operations, improvements in business relationships, market growth (Pflughoeft et al, 2003), (Zhu and Kraemer, 2005), (Zhu et al, 2006), (Fuchs et al, 2010), contributions of e-commerce to the achievement of organizational goals, the number of visitors to a particular site, the amount of time visitors spend on a particular site (Quaddus & Achjari, 2005), strategic benefits (Pflughoeft, 2003), the number of applications used (Yuan et al, 2003), and competitive advantage (Elly & Boter, 2011).…”
Section: Effects Of E-commerce On Firm Performancementioning
confidence: 99%
“…The widespread adoption and increased use of the web for e-commerce are driven by IT sophistication as well as by lower web-related costs (Pflughoeft et al, 2003). Yuan et al (2003) used the number of years an organization has used internet applications and the number of internet applications an organization uses to define e-commerce use. Kraemer et al (2005) measured the extent of e-commerce use in terms of the type of use (e.g., B2B and B2C) and the scope of use, and Gibbs and Kramer (2010) defined it as the extent to which e-commerce is used in various values chain activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar concept is Convention and Visitor Bureau, characterized as a small or medium non-profit organization, which makes a wide range of information and communication activities to facilitate the development and promotion of tourism in certain geographic areas (Yuan, Gretzel y Fesenmaier, 2003).…”
Section: From Citymarketing To Citybrandingmentioning
confidence: 99%
“…In the academic literature many tourism re- Gretzel, & Fesenmaier, 2003). A third area of research has reported on the searchers have studied the Internet as a distribution channel for a variety of travel products.…”
Section: Introductionmentioning
confidence: 99%